Support for Process of Knowledge Commercialization and Integration of Academic Community with Economic Environment - Szewczuk-Stępień, Marzena (Regional Barometer. Analyses & Prognoses, 2017)
The aim of the paper is to present the idea of innovation and the results of implementing the program “Innovation Brokers” against the background of barriers and limitations to the effective process of knowledge transfer. The paper reports the results of a study into commercialization of the results of research, knowledge and technology transfer as well as the support for development based on innovations. The contributions to the discussion and the analysis are based on the completion of the “Innovation Brokers” program as well as identification of a global trend involving the activity of various environments aimed at the creation and development of an innovation ecosystem.